Kidney damage in burn disease. Part 1. Pathomorphophysiology (literature review) - Kravets, O.V.; Yekhalov, V.V.; Gorbuntsov, V.V.; Krishtafor, D.A. (KIDNEYS, 2023)
Acute kidney injury (AKI) is a common complication in critically ill burn patients and is associated with serious adverse outcomes, including increased length of hospital stay, development of chronic kidney disease, and increased risk of mortality. The incidence of AKI among burn patients in the intensive care units is 38 (30–46) %. A high percentage of the total burn surface area and a number of individual predisposing factors are considered to be the leading risk factors for AKI. Pathophysiological and morphological changes in the body under the combination of burn disease and kidney damage have certain discrepancies with the classical course of the pathological process in some nosological forms. Despite significant progress in the technologies of fluid resuscitation, intensive care and renal replacement therapy in recent years, the morbidity and mortality rate in such patients remain quite significant. A better understanding of clinical characteristics, early detection and prevention of risk factors for kidney damage in burns, as well as timely medical intervention can effectively reduce morbidity and progression of the pathological process, and also optimize the prognosis in the long run.